Persepsi Dan Komunikasi Dalam Organisasi Pendidikan - Musdhalifa, Dhea; Syaifudin, Muhammad (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
This perception and communication is very important to know because it understands behavioral science. Communication occurs when someone wants to convey information to others. And this communication can work properly and correctly and if the delivery of the information conveys it properly, and the recipient of the information receives it not in the form of a ride. Perception is essentially a cognitive process experienced by everyone in understanding information about their environment, through sight, hearing, appreciation, feeling and smell. Communication is the process of conveying information from one person to another, either by telephone, letter, conversation, expression, a combination of these methods, and so on. In essence, perception is a process of evaluating a person against a particular object. Because perception is an activity of sensing, integrating and providing an assessment of physical objects and social objects, and this sensing depends on physical and social stimuli in the environment. In the process of individual perception required to provide an assessment of an object that can be positive/negative, happy or not happy and so on. With the existence of perception, attitudes will be formed, namely a stable tendency to apply or act in a certain way in certain situations